Nutrient Digestibility and Apparent Bioavailability of Minerals in Beef Cattle Fed with Different Levels of Concentrate and Oil-palm Fronds - Warly, Lili; Suyitman; Evitayani; Fariani, Armina (Pakistan Journal of Nutrition, 2017)
Objective: This experiment was carried out to determine the effects of various levels of concentrate and oil-palm fronds (OPF) on nutrient digestibility and apparent mineral bioavailability in beef cattle. Materials and Methods: Fifteen Simmental cattle were allocated to three experimental diets in a random block design. Dietary treatment 1 (diet 1) contained 40% concentrate and 60% OPF, dietary treatment 2 (diet 2) contained 50% concentrate and 50% OPF and dietary treatment 3 (diet 3) contained 60% concentrate and 40% OPF. The concentrate consisted of rice bran, tofu waste and ex-decanter solid waste from palm-oil processing, no mineral supplement was given in this study. Results: The results of the study showed that the digestibility of dry matter, crude fiber, crude protein, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and cellulose were significantly higher (p